2010
DOI: 10.1038/mp.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 in the brain: genotype effects on resting brain perfusion

Abstract: The cytochrome P450 2D6 (CYP2D6) is a genetically polymorphic enzyme involved in the metabolism of several psychoactive drugs. Beside its expression in the liver, CYP2D6 is highly expressed in several regions of the brain, such as the hippocampus, thalamus, hypothalamus and the cortex, but its function in the brain is not well understood. The CYP2D6 enzyme may also have a physiological role due to its involvement in neurotransmitter biotransformation. In this study, CYP2D6 genotyping was performed in N = 188 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…Two genetic neuroimaging studies on separate samples reported an association between specific brain areas and CYP2D6 genotypes. Kirchheiner et al 108 tested the existence of such an association in rest perfusion levels in healthy participants, detecting an effect of CYP2D6 polymorphism on rest perfusion in the thalamus, hypothalamus, posterior cerebral cortex and isolated parts of the medial temporal lobe and orbitofrontal cortex, with PMs having higher perfusion levels (see Figure 4). This pattern suggested an association with brain circuits involved in vigilance.…”
Section: Polymorphic Dmes In the Brainmentioning
confidence: 96%
“…Two genetic neuroimaging studies on separate samples reported an association between specific brain areas and CYP2D6 genotypes. Kirchheiner et al 108 tested the existence of such an association in rest perfusion levels in healthy participants, detecting an effect of CYP2D6 polymorphism on rest perfusion in the thalamus, hypothalamus, posterior cerebral cortex and isolated parts of the medial temporal lobe and orbitofrontal cortex, with PMs having higher perfusion levels (see Figure 4). This pattern suggested an association with brain circuits involved in vigilance.…”
Section: Polymorphic Dmes In the Brainmentioning
confidence: 96%
“…[13][14][15]19 Some of the earliest indications that brain CYPs may have important neurologic endogenous functions came from personality testing, where individuals with a CYP2D6 poor metabolizer genotype and phenotype were observed to have different personality traits than CYP2D6 normal metabolizers. 65 Several studies of this type have shown an effect of genetic variability in CYP2D6 on personality, [66][67][68] and recently this has been linked more closely to the brain in reports where different CYP2D6 genotypes were found to be associated with different resting brain perfusion rates 69 and with different levels of brain activation during a cognitive task. 70 Similar associations of genotype and personality or mood have been observed for CYP2C19, CYP2E1 and CYP19 (aromatase).…”
Section: Endogenous Brain Cyp Functionmentioning
confidence: 99%
“…These patterns are visible when statistical parametric maps are thresholded at uncorrected levels to display the estimated effects. In our work, CASL was applied to study individual differences in baseline perfusion defined by psychological variables or genotypic variants (Abler et al, 2008;Beschoner et al, 2008;Kirchheiner et al, 2010;Viviani et al, 2010a). We noted that the same patterns tended to arise in t maps of linear estimates of individual differences, even if the explanatory variables used across studies had little relation to each other, sometimes confounding the interpretation of clusters of effects.…”
Section: Introductionmentioning
confidence: 93%